2017
DOI: 10.1016/j.asjsur.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Survival after surgical resection of distal cholangiocarcinoma: A systematic review and meta-analysis of prognostic factors

Abstract: In general, prognosis of DCC after resection is poor. R0 resection results in a substantially improved survival and represents one of the most important prognostic variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
55
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 45 publications
8
55
1
7
Order By: Relevance
“…Tumor differentiation and LN metastases were identified as important predictors of survival in our study, as demonstrated in other studies [2-5,7,12]. In particular, a meta-analysis conducted by Zhou et al [13] revealed that LN metastasis was associated with shorter OS (risk ratio, 2.35; 95% confidence interval, 1.89 to 2.93; p < 0.0001). Most studies included in this meta-analysis reported that LN metastasis has a powerful negative effect on survival.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Tumor differentiation and LN metastases were identified as important predictors of survival in our study, as demonstrated in other studies [2-5,7,12]. In particular, a meta-analysis conducted by Zhou et al [13] revealed that LN metastasis was associated with shorter OS (risk ratio, 2.35; 95% confidence interval, 1.89 to 2.93; p < 0.0001). Most studies included in this meta-analysis reported that LN metastasis has a powerful negative effect on survival.…”
Section: Discussionsupporting
confidence: 86%
“…A positive resection margin has been considered as an adverse prognostic factor in some studies [6,7,11,13]; however, its prognostic impact has not been fully determined because of inconsistent results among studies and diverse definitions. Incidences of a positive resection margin in EHBD cancer after curative resection can vary from 10% to as high as 70%, which can be explained by differences between surgeons regarding the principle of the operation or the definition of a positive resection margin, such as whether to include carcinoma in situ [15-19].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors, including pancreatic invasion, lymph node metastasis, resection margin status, tumor grade, lymphatic invasion, perineural invasion, vascular invasion, type of preoperative biliary drainage, and postoperative pancreatic fistula, have been reported to be associated with poor prognostic outcome in patients with DCC who undergo surgical resection [18-22]. However, most of these predictive factors can be determined only after surgery, and some are not objective, and thus they would not improve treatment decision-making or help implement stratification strategies preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, patients with early-stage HCC can be offered a potentially curative approach if the tumors are found to be resectable [7]. In patients with CCC, who generally have a poor prognosis, surgical resection again represents the only potential strategy to permanently eradicate the disease [810]. …”
Section: Introductionmentioning
confidence: 99%